Reactive species balance via GTP cyclohydrolase I regulates glioblastoma growth and tumor initiating cell maintenance. Issue 8 (2nd February 2018) - Tran, Anh Nhat; Walker, Kiera; Harrison, David G; Chen, Wei; Mobley, James; Hocevar, Lauren; Hackney, James R; Sedaka, Randee S; Pollock, Jennifer S; Goldberg, Matthew S; Hambardzumyan, Dolores; Cooper, Sara J; et al.
Abstract: Background: Depending on the level, differentiation state, and tumor stage, reactive nitrogen and oxygen species inhibit or increase cancer growth and tumor initiating cell maintenance. The rate-limiting enzyme in a pathway that can regulate reactive species production but has not been thoroughly investigated in glioblastoma (GBM; grade IV astrocytoma) is guanosine triphosphate (GTP) cyclohydrolase 1 (GCH1). We sought to define the role of GCH1 in the regulation of GBM growth and brain tumor initiating cell (BTIC) maintenance. Methods: We examined GCH1 mRNA and protein expression in patient-derived xenografts, clinical samples, and glioma gene expression datasets. GCH1 levels were modulated using lentiviral expression systems, and effects on cell growth, self-renewal, reactive species production, and survival in orthotopic patient-derived xenograft models were determined. Results: GCH1 was expressed in GBMs with elevated but not exclusive RNA and protein levels in BTICs in comparison to non-BTICs. Overexpression of GCH1 in GBM cells increased cell growth in vitro and decreased survival in an intracranial GBM mouse model. In converse experiments, GCH1 knockdown with short hairpin RNA led to GBM cell growth inhibition and reduced self-renewal in association with decreased CD44 expression. GCH1 was critical for controlling reactive species balance, including suppressing reactive oxygen species production, which mediated GCH1 cell growth effects. In silico analyses demonstrated that higher GCH1 levels in glioma patients correlate with higher glioma grade, recurrence, and worse survival. Conclusions: GCH1 expression in established GBMs is pro-tumorigenic, causing increased growth due, in part, to promotion of BTIC maintenance and suppression of reactive oxygen species.